2000
DOI: 10.1002/(sici)1097-0088(200002)20:2<171::aid-joc471>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and interannual rainfall variability in Uganda: implications for agricultural management

Abstract: The El Niñ o-Southern Oscillation (ENSO) is correlated with the short rainy season (September -December) in East Africa. Seasonal climate forecasts made on this basis are being disseminated in the hope that this information will be useful in regional or even local planning and resource management. In order to improve the likelihood of success in using regional forecasts in Uganda, particularly in the agricultural sector, climate analysis was performed at the sub-regional level with distinctions being made betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 0 publications
7
39
0
Order By: Relevance
“…On average the MAM and SON totals accounted for 76 % of the mean rainfall in the water management area. Evidence of this seasonality was also reported by Ogallo (1984), Basalirwa (1995), and Nicholson (1996) and later used by Phillips and McIntyre (2000) to delineate Uganda into sites of uni-and bimodal rainfall distribution patterns. Beltrando (1990) attributed this distribution pattern to the seasonal movements of the ITCZ.…”
Section: Seasonal Rainfall Seriessupporting
confidence: 65%
See 2 more Smart Citations
“…On average the MAM and SON totals accounted for 76 % of the mean rainfall in the water management area. Evidence of this seasonality was also reported by Ogallo (1984), Basalirwa (1995), and Nicholson (1996) and later used by Phillips and McIntyre (2000) to delineate Uganda into sites of uni-and bimodal rainfall distribution patterns. Beltrando (1990) attributed this distribution pattern to the seasonal movements of the ITCZ.…”
Section: Seasonal Rainfall Seriessupporting
confidence: 65%
“…These features introduce significant modification in the general wind patterns over the region, coupled with convection processes that generate a climatic pattern, which is complex and changes rapidly over short distances (Nicholson 1996). These climatic processes result into a bimodal pattern of rainfall, with the primary rainy season occurring in March-May and a shorter secondary rainy season occurring in October-December (Phillips and McIntyre 2000).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of rainfall pattern over Uganda is related to the movement of the ITCZ, which brings rainfall approximately 1 month after the sun's migration north or south resulting in a bi-modal rainfall pattern, with the primary rain season occurring in MAM, and a shorter secondary rainy season occurring in October-November-December (OND) (Nicholson 1996, Kizza et al 2009). Phillips and Mcintyre (2000) attribute moisture during OND to the northeasterly winds originating in the Indian Ocean. However, the northern sub-basins, which have peaks in August, receive moisture from the Congo/ Zaire basin to the southwest.…”
Section: Rainfall Characteristicsmentioning
confidence: 99%
“…Nicholson (1996) also revealed that interannual variability of rainfall is remarkably coherent throughout most of eastern Africa, especially during the October-December season, with a dominant time scale of variability of 5-6 years. Phillips and Mcintyre (2000) investigated Pacific El Niño-Southern Oscillation (ENSO) and inter-annual rainfall variability in relation to agricultural management in Uganda. They discovered that Pacific Ocean NINO3 region sea-surface temperatures (SSTs) from July to September are significantly correlated with both August-September and November-December rainfall, but with opposite signs.…”
Section: Introductionmentioning
confidence: 99%